2018
DOI: 10.1371/journal.pone.0203367
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue interventions in long term, physical health conditions: A scoping review of systematic reviews

Abstract: ObjectiveFatigue is prominent across many long term physical health conditions. This scoping review aimed to map the fatigue intervention literature, to ascertain if certain interventions may be effective across conditions, and if novel interventions tested in specific long term conditions may be promising for other conditions.MethodsScoping review methodological frameworks were used. Electronic bibliographic databases were searched (inception to November 2016) for systematic reviews of fatigue interventions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…However, studies differed widely in terms of mode, duration and frequency of the intervention delivery. This has also been reported in other reviews of non-pharmacological interventions for fatigue [66]. There were also differences in the extent of contact across the different interventions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, studies differed widely in terms of mode, duration and frequency of the intervention delivery. This has also been reported in other reviews of non-pharmacological interventions for fatigue [66]. There were also differences in the extent of contact across the different interventions.…”
Section: Discussionsupporting
confidence: 80%
“…As noted in similar reviews [6870], the generalisability of the findings are limited due to the high proportion of studies that focused specifically on breast cancer or recruited a disproportionate number of breast cancer survivors. The majority of studies did not specifically target fatigue or screen for fatigue as part of inclusion criteria as recommended in existing guidelines [1, 6, 66]. Few studies described the cancer treatment received by participants in detail, such as types of treatments and total duration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews indicate that exercise and cognitive behavioural therapy (CBT) are common non-pharmacological interventions with potential efficacy in reducing fatigue. 24 Very few studies have explored fatigue in PLWH, and most of the reviews to date have included multiple physical problems, adding complexity in the interpretation of the results in PLWH. One review focusing on PLWH with advanced illness found that progressive resistive exercise and aerobic exercise were effective but the results cannot be expanded to the general PLWH who are in earlier stages of illness.…”
Section: Description Of Interventionmentioning
confidence: 99%
“…Findings from previous symptom research studies involving middle‐aged adults with IBD indicate that fatigue is the most prevalent symptom (Conley et al, ; Farrell et al, ). Fatigue is an overwhelming sense of tiredness, lack of energy, and feeling of exhaustion (Hulme et al, ). Fatigue is not simply due to the effects of treatment because fatigue is common among recently diagnosed patients (Cohen et al, ) as well as those with the long‐standing disease (Huppertz‐Hauss et al, ).…”
Section: Introductionmentioning
confidence: 99%